Penerapan Tema Ekologi pada Perencanaan dan Perancangan Pusat Konservasi Penyu di Pulau Serangan Denpasar: Bahasa indonesia - Mahendra, Kadek Dwi Yoga; Kurniawan, Agus; Nurwarsih, Ni Wayan; Wicaksana, Gde Bagus Andhika; Utari, Cokorda Istri Arina Cipta (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2024)
Turtles, endangered marine reptiles, are internationally protected and regulated by national laws in Indonesia. Despite conservation efforts, research indicates a significant decline in turtle populations due to environmentally unfriendly exploitation. Bali has the potential to serve as a turtle nesting site, but existing conservation facilities are not optimal. The facilities in Bali lack attention to the needs of turtles, and limited infrastructure hampers the development of breeding grounds, especially with a shortage of research facilities. This phenomenon is feared to jeopardize the sustainability of turtle populations and damage their habitats. As a solution, a facility is proposed that integrates turtle conservation and educational tourism on Serangan Island, Bali. The design is not only recreational and educational but also meets technical conservation requirements. Serangan Island is chosen for its safety for turtles, being far from settlements, and strategically located for turtle migration. This research is a qualitative descriptive research with data collection methods in the form of observation and literature study. The Turtle Conservation Center on Serangan Island is planned with the basic concept of sustainable architecture, integrating environmental science and architecture to achieve comprehensive sustainability and the theme of Ecological Architecture, maintaining the balance of natural and artificial environments. Thus, the presence of the Conservation Center is expected to not harm the environment and increase public awareness of the importance of turtle conservation.